The activity of a yeast Family 16 methyltransferase, Efm2, is affected by a conserved tryptophan and its N‐terminal region - Joshua J. Hamey; Gene Hart‐Smith; Melissa A. Erce; Marc R. Wilkins (FEBS Open Bio, 2016)
The Family 16 methyltransferases are a group of eukaryotic nonhistone protein methyltransferases. Sixteen of these have recently been described in yeast and human, but little is known about their sequence and structural features. Here we investigate one of these methyltransferases, Saccharomyces cerevisiae elongation factor methyltransferase 2 (Efm2), by site‐directed mutagenesis and truncation. We show that an active site‐associated tryptophan, invariant in Family 16 methyltransferases and at position 222 in Efm2, is important for methyltransferase activity. A second highly conserved tryptophan, at position 318 in Efm2, is likely involved in S‐adenosyl methionine binding but is of lesser consequence for catalysis. By truncation analysis, we show that the N‐terminal 50–200 amino acids of Efm2 are critical for its methyltransferase activity. As N‐terminal regions are variable among Family 16 methyltransferases, this suggests a possible role in determining substrate specificity. This is consistent with recently solved structures that show the core of Family 16 methyltransferases to be near‐identical but the N termini to be structurally quite different. Finally, we show that Efm2 can exist as an oligomer but that its N terminus is not necessary for oligomerisation to occur.